통합 교통서비스 발전 방향 탐색을 위한 사용자 리뷰 기반 국내 MaaS(Mobility as a Service) 현황 및 실태 분석 - 김동건; 강주영 (정보시스템연구, 2024)
Purpose The purpose of this study is to promote the development of domestic Moility as a Service(MaaS) by analyzing user reviews from existing MaaS. We seek to identify the topics mentioned for each service and derive the ratings of these topics to understand the strengths and weaknesses. Design/methodology/approach This study evaluated and classified 10 domestic MaaS based on the components derived from previous research, collected user reviews for each service from the Google Play Store and conducted topic modeling using LDA. Findings The study results showed that the topic of 'pricing' was the most frequently mentioned, while the topics of 'UI & UX', 'registration and sign-up', and 'customer service' received low ratings of less than 3 points across all services where these topics were identified. Therefore, it is necessary to improve UI & UX based on user feedback, implement a simpler registration process to enhance accessibility, and improve customer service through regular staff training, diverse communication channels, and faster response times.
Keywords: Mobility as a Service(MaaS); Service Review; Topic Modeling; LDA